Military trials of war criminals in the Netherlands East Indies 1946-1949 - Borch, Frederic L., 1954- (Oxford : Oxford University Press, 2017)
This title examines and analyses the records of the Dutch war crimes tribunals from 1946-1949, which prosecuted more than 1000 Japanese soldiers and civilians for war crimes committed during the occupation of the Netherlands East Indies during World War II.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 18, 2017).
Keywords: War crime trials -- Indonesia -- History -- 20th century; World War, 1939-1945 -- Atrocities -- Indonesia; Law; International law